Любительское рыболовство и охрана природы - Семенова Галина Николаевна (Росагропромиздат, 1991)
Экземпляры: б/ф №3 (20180320) / Инвентарный номер: 18281 / Цена: 2.40 / Авт.знак: Л 93 / ГРНТИ: 68 / ББК: 47.22